Informed consent comprehension among vulnerable populations in Ecuador: video-delivered vs. in-person standard method. (4th July 2018) - Quevedo, Ana; Condo, Cecilia; Valenzuela, Gilda; Molina, Lucy; Castillo, Eduardo; Palacio, Ana; Pareja, Denisse; Prado, Guillermo; Estrada, Yannine; Velazquez, Maria Rosa; Tamariz, Leonardo
ABSTRACT: The informed consent comprehension process is key to engaging potential research subject participation. The aim of this study is to compare informed consent comprehension between two methods: standard and video-delivered. We compared the in-person and video-delivered informed consent process in the Familias Unidas intervention. We evaluated comprehension using a 7-item true/false questionnaire. There were a total of 152 participants in the control group and 87 in the experimental. General characteristics were similar between both groups ( p  > 0.05). First-attempt informed consent comprehension was higher in the intervention group but was not statistically significant (80% and 78% respectively p  = 0.44). A video-delivered informed consent process did not differ from the standard method of informed consent in a low educational and socioeconomic environment.